A Review of the Islamic Perspective on Consumer Behaviors - Nur Jamaludin; Luqman Hakim Handoko; Mohd Nazrul Nazrul Katek; Mohd Sukhor Bin Abdullah (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2022)
Modern economic theory focuses heavily on how consumers select how much to consume now and how much to save for the future. This is a major aspect of consumer behavior (Khan, 1984). Related to this statement, the article by Prof. Muhammad Annas Zarqa has pointed to an issue that is crucial because this is likely to be one of the main questions that economists would be worried about. Thus, this paper has two aims, the first of which is to examine the notion of consumer behavior in Islamic economics. While the specific objectives were to emphasize that not all traditional theories are compatible with Muslim consumer behavior, to demonstrate that Islamic injunctions and rules related to consumption should not be introduced as constraints on consumer behavior, and to indicate the interdependence between the utility of different Muslims, attempts were made to modify consumer behavior related to shari'ah. This research uses qualitative methodology. In conclusion, Zarqa believes that the existing consumer theory must be modified to accommodate Muslim consumers. Then he addressed the point that the distinction between the preference function and the utility function should be examined in Shariah. Because classical economics considered that customer behavior must be based on the utility function in order to be satisfying, Zarqa has proposed that this problem be explored and further investigated utilizing the empirical method, without regard to the Islamic prohibition on consumer behavior.